Study of horizontal and vertical uniformity of B-doped layer on mosaic single crystal diamond wafers by using hot-filament chemical vapor deposition. Issue 1 (31st December 2022) - Yamada, Hideaki; Shimaoka, Takehiro
Abstract: Aiming at developing inch-sized processing of diamond, B-doped layer was grown on mosaic single-crystallin diamond wafers by using hot-filament chemical vapor deposition (CVD), which is expected to have an advantage in terms of the deposition area compared with microwave plasma (MWP) CVD. Uniformity in horizontal and vertical directions is studied. It is found that the junctions of the monocrystalline diamond domains in the mosaic wafer and the direction of the crystal off-angles against to these junctions are less effective to the uniformity of the impurity concentrations. On the other hand, it is suggested that excess incorporation of W from the filament suppresses the growth and incorporation of B. It is shown that millimeter scale or more precise control of the arrangement of the wafer and the filament enables to obtain more uniform and efficient doping.